Delmar's firefighter's handbook video series. - Rutledge, Marty; Light & Power Communications (Firm); Delmar Learning (Albany, N.Y. : Delmar Thomson Learning, 2002)
Provides information about the use and care of personal and protective firefighting equipment, including a step-by-step overview of the processes and procedures used every day by highly trained firefighters on the job.
v. 1. Personal protective equipment (18 min.) -- v. 2. Self contained breathing apparatus (20 min.) -- v. 3. Portable fire extinguishers (16 min.) -- v. 4. Ladders (25 min.).
DVD